Comparative Evaluation of Genetic Algorithm and Modification of Agglomerative Method for Allocating New Students - Zainudin Zukhri; Khairuddin Omar (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Allocating new students into their classes is a clustering problem, that is how to cluster new students intotheir classes so that each class contains students in the number that less than or equals to its capacity and hasminimum gap of intelligence. It needs a suitable method to avoid an educational problem. This paper describesthe comparison of Genetic Algorithm (GA) and Modification of Agglomerative Methods (AM) for solving thisproblem. To determine which method is better then the other, the software of each method which can cluster nstudents with m attributes into c classes are evaluated by two-dimensional random data consists of 200 students.Then we compare the results. Comparison of GA and AM for clustering the data sets shows that although the GAcluster the data successfully, the method provides no advantages over AM. Intelligence gap of students in eachclass clustered by GA almost same each other, but the average of this value is greater than by AM. Meanwhile,the intelligence gap of student clustered by AM depend on the clustering sequence. This GA performance may beis caused by unsuitable GA approach, both chromosome representation and GA operators in this research.Better GA approach may enhance the effectiveness of the GA searching.Keywords: Agglomerative Method, cluster, Genetic Algorithm, student.